2006
DOI: 10.1109/jlt.2005.862446
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of bit error rate in cascaded 2R regenerators

Abstract: Abstract-This paper presents a simple and efficient model for estimating the bit error rate (BER) in a cascade of optical reamplification and reshaping (2R) regenerators. The model includes the influences of amplifier noise, finite extinction ratio (ER), and nonlinear reshaping. The interplay between the different signal impairments and the regenerating nonlinearity is investigated. It is shown that an increase in nonlinearity can compensate for an increase in noise figure or decrease in signal power. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…We show below that this is indeed possible and besides resulting in net gain it also allows control of the amplitude of the output signal. In addition, the cascading of several alternating gain and absorber sections may result in a reduction of the noise [23,24].…”
Section: Multisection Devicesmentioning
confidence: 99%
“…We show below that this is indeed possible and besides resulting in net gain it also allows control of the amplitude of the output signal. In addition, the cascading of several alternating gain and absorber sections may result in a reduction of the noise [23,24].…”
Section: Multisection Devicesmentioning
confidence: 99%
“…It is shown that a receiver-sensitivity improvement of 4 dB at a BER of 10 -9 in the case of signal with ER = 3.87 dB, while for ER = 6.79 dB an improvement of 2 dB is achieved. With these results a BER improvement in a cascade regenerator [5] is demonstrated. OSNR measurements results are given in Fig.…”
Section: Experimental Resulsmentioning
confidence: 70%
“…In order to reduce this effect, the first SOA in the device should have as large a gain as possible [11]. Furthermore, the increase in nonlinearity can, if large enough, compensate for the higher noise figure by improving the redistribution of noise [6], [12]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The important properties of the intensity transfer function are large attainable ER, strong nonlinearity, and the possibility to adjust the power threshold that separates the one-and zerolevels [6]. In this letter, we demonstrate experimentally that these properties are achieved in the SOA-EA regenerator by concatenating several amplifying and absorbing sections and by using proper bias conditions.…”
mentioning
confidence: 85%